Role of novel cardiac biomarkers for the diagnosis, risk stratification, and prognostication among patients with heart failure - Miao, Jennifer; Estis, Joel; Su, Yan Ru; Todd, John A; Lenihan, Daniel J (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Current guidelines for diagnosis and management of heart failure (HF) rely on clinical findings and natriuretic peptide values, but evidence suggests that recently identified cardiac biomarkers may aid in early detection of HF and improve risk stratification. The aim of this study was to assess the diagnostic and prognostic utility of multiple biomarkers in patients with HF and left ventricular systolic dysfunction (LVSD). Methods: High-sensitivity cardiac troponin I (cTnI), N-terminal pro b-type natriuretic peptide (NT-proBNP), interleukin-6 (IL-6), endothelin-1 (ET-1), pro-matrix metalloproteinase-9 (pMMP-9), and tumor necrosis factor-alpha (TNF-α) were measured using single-molecule counting technology in 200 patients with varying stages of HF. Plasma detection with cross-sectional associations of biomarkers across all HF stages, and advanced-therapy and transplant-free survival were assessed using multivariate analysis and Cox regression analyses, respectively. Results: NTproBNP, pMMP-9, IL-6 were elevated in early, asymptomatic stages of HF, and increased with HF severity. Higher circulating levels of combined IL-6, NTproBNP, and cTnI predicted significantly worse survival at 1500-day follow-up. Cox regression analysis adjusted for ACC/AHA HF stages demonstrated that a higher concentration of IL-6 and cTnI conferred greater risks in terms of time to death, implantation of left ventricular assist device (LVAD), or heart transplantation. Conclusion: Biomarkers of inflammation, LV remodeling, and myocardial injury were elevated in HF and increased with HF severity. Patients had a significantly higher risk of serious cardiac events if multiple biomarkers were elevated. These findings support measuring NTproBNP, cTnI and IL-6 among patients with HF and LVSD for diagnostic and prognostic purposes.